MINERALOGICAL-GENETIC MODEL OF THE ZAVALLYA GRAPHITE DEPOSIT - Goshovskiy, S.; Rosliy, I.; Bobrov, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The radioactive analysis of the anomalies being situated there where the boreholes are drilled, has been performed and the uranium concentrations of the underground water, at the territory of the north-western borderlands of the Dnieper-Donetsk cavity, have been studied. The presence of five uranium-bearing zones where uranium fields being forecasted at different depths, has been substantiated. The zones are situated at the places of intersections of the Pre-Cambrian deep-seated and the Devonian riftogeneous crust-mantle fractures. The primary sources of uranium mineralization of the sedimentary rocks are primary deposits and shows of ore of the crystalline foundation, hydrothermal fluids supplied through fractures and infiltrational solutions having uranium, too. The uranium-bitumen metallization, in the uranium-bearing zones, has been supposed